Mass spectrometric study of the laser‐evaporated Fe–Zr–O system up to 3300 K. Issue 3 (2nd November 2021) - Sheindlin, Michael; Frolov, Alexander; Petukhov, Sergei; Bottomley, David; Masaki, Kurata; Manara, Dario; Costa, Davide
Abstract: Material systems such as U–Zr–O, Fe–Zr–O, and Zr–O have been recognized as fundamental for the analysis of in‐vessel nuclear fuel debris behavior during a severe meltdown accident. In the present work, the evaporation behavior of ZrO2 and Zr–Fe–O systems are investigated using heating with laser pulses of millisecond duration and time‐of‐flight mass spectrometry. The relative partial pressures of main species of vapor over ZrO2 and ZrO2 –FeO systems were measured at temperatures above 2750 K. The temperature dependence of O/Zr atomic ratio in vapor over zirconia was analyzed: it turned out that evaporation occurs in a noncongruent mode at temperatures above 3000 K. Evaporation of the Zr–Fe–O system was greatly affected by the fast evaporation of FeO, implying that the atomic Zr/Fe ratio, less than 0.1 below 3000 K, significantly increased with temperature. Moreover, the ratios of main vapor components were defined only by the surface temperature, independent of the zirconia sample origin.